Experimental Modal Analysis – A Tool for Unbalance Identification of Rotating Machines - T. Kreuzinger-Janik; H. Irretier (International Journal of Rotating Machinery)
In this paper a method is proposed for unbalance identification ofelastic rotors. The method is essentially based on the rotordynamic theory combined with experimental modal analysis and allows to identify the unbalance distribution on the complete rotor. A rotor test rig designed for rotordynamic experiments, modal analysis and especially for the unbalance identification has been developed. It allows an arbitrary excitation with a particularly developed noncontact magnetic exciter, as well as measuring vibrations in radial direction with non-contact laser sensors and eddy currents. Special effects of rotordynamic like anisotropic journal bearings and gyroscopic forces can be simulated. Experimental and theoretical results like mode shapes and unbalance parameters for the laboratory model are presented in detail.